Knowledge, beliefs and attitudes of equine practitioners and enthusiasts about behaviors, emotions and welfare in horses - Maurício, Letícia Santos (2023)
Tese (doutorado) ? Universidade Federal de Santa Catarina, Centro de Ciências Agrárias, Programa de Pós-Graduação em Agroecossistemas, Florianópolis, 2023.